2011
DOI: 10.1177/0267659111415564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of minimized cardiopulmonary bypass with conventional techniques on the incidence of retinal microemboli during aortic valve replacement surgery

Abstract: The use of MCPB was associated statistically insignificantly with less retinal microemboli compared to CCPB. MCPB was complicated by excess bleeding and need for transfusion. The feasibility of MCPB techniques in valve surgery requires further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…A similar trend was observed by a group studying the incidence of retinal microembolism in patients undergoing SAVR with CECC or MiECC. Microemboli count did not differ but following MiECC there were fewer perfusion defects on retinal fluorescein angiographs (41). Another group compared three different miniaturized extracorporeal systems with CECC in CABG surgery, and did not note increased microbubble generation with MiECC (42).…”
Section: Discussionmentioning
confidence: 96%
“…A similar trend was observed by a group studying the incidence of retinal microembolism in patients undergoing SAVR with CECC or MiECC. Microemboli count did not differ but following MiECC there were fewer perfusion defects on retinal fluorescein angiographs (41). Another group compared three different miniaturized extracorporeal systems with CECC in CABG surgery, and did not note increased microbubble generation with MiECC (42).…”
Section: Discussionmentioning
confidence: 96%
“…Remadi et al 7 likewise reported on a significant reduction in perioperative RBC transfusion of 9% versus 16% in a similar study. On the other hand, Kobayashi et al 11 and Rimpilainen et al 12 found similar transfusion rates for RBC in their prospective randomized studies on MiECC versus CECC in AVR. However, both studies were relatively small (13-20 patients in each group) and both had a high re-transfusion volume from the cell saver in their MiECC groups (304 ± 369 ml and 1520 ± 969 ml, respectively).…”
Section: Discussionmentioning
confidence: 84%
“…Although these patient numbers are limited, most prospective randomized studies in this field have involved group sizes of 50 patients or less 7,[8][9][10][11][12] and none of the studies, to date, has dealt specifically with octogenarians. 7,[8][9][10][11][12][13] In fact, almost all the studies involved lowrisk patients, hence, it is not surprising that their results showed either no mortalities 7,8,[10][11][12][13] or no differences in mortality. 9 In comparison, our study shows differences in the 30-day postoperative mortality (2% vs. 10%), but these lack statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein is primarily used in eye diagnostics and retinal angiography studies, 25,57,191 including measurements of retinal perfusion 177 but its use in other applications has been considered for example in cranial base surgery, 152 thoracoscopy, 143 glioma surgery, 114 colorectal cancer 124 or to monitor aortic valve replacement surgery. 159 In addition to fluorescein, indocyanine green (ICG) 168 has also been considered as an alternative organic dye for optical imaging applications operating in the near-infrared. Since operation in the near-infrared allows imaging deeper than in the visible, ICG has been more recently employed in several interventional applications, for example for sentinel lymph node (SLN) identification in breast, 202 gastric, 101 cervical 34 and vulvar 33 cancer, for angiography during reconstructive surgery, 39,73,113,185,210 skin flap perfusion, 78 lymphatic drainage mapping 1,172 and for imaging of glioma 70 and liver cancer 66,89 and metastases.…”
Section: Epi-illumination Fluorescence Imaging (Exogenous Contrast)mentioning
confidence: 99%